Antitubercular activity assessment of fluorinated chalcones, 2-aminopyridine-3-carbonitrile and 2-amino-4H-pyran-3-carbonitrile derivatives: In vitro, molecular docking and in-silico drug likeliness studies - Lagu, Surendra Babu; Yejella, Rajendra Prasad; Nissankararao, Srinath; Bhandare, Richie R.; Golla, Venu Sampath; Subrahmanya Lokesh, Bontha Venkata; Rahman, M. Mukhlesur; Shaik, Afzal Basha (PLOS ONE, 2022)
A series of newer previously synthesized fluorinated chalcones and their 2-amino-pyridine-3-carbonitrile and 2-amino-4H-pyran-3-carbonitrile derivatives were screened for their in vitro antitubercular activity and in silico methods. Compound 40 (MIC 8 μM) was the most potent among all 60 compounds, whose potency is comparable with broad spectrum antibiotics like ciprofloxacin and streptomycin and three times more potent than pyrazinamide. Additionally, compound 40 was also less selective and hence non-toxic towards the human live cell lines-LO2 in its MTT assay. Compounds 30, 27, 50, 41, 51, and 60 have exhibited streptomycin like activity (MIC 16–18 μM). Fluorinated chalcones, pyridine and pyran derivatives were found to occupy prime position in thymidylate kinase enzymatic pockets in molecular docking studies. The molecule 40 being most potent had shown a binding energy of -9.67 Kcal/mol, while docking against thymidylate kinase, which was compared with its in vitro MIC value ( 8 μM). These findings suggest that 2-aminopyridine-3-carbonitrile and 2-amino-4H-pyran-3-carbonitrile derivatives are prospective lead molecules for the development of novel antitubercular drugs.